«VERBAL SCENERY»: BASIC TERMINOLOGY AND STRUCTURAL PARAMETERS - V. P. Khodus; V. V. Sichinava (Гуманитарные и юридические исследования)
The paper considers main approaches, differential features and criteria of specifying the "verbal scenery" in the drama. The role and functions of the scenery in the acting space are presented and the general classiication of the scenery is described. Despite the activity of studying theatrical space, outside the ield of view are important elements, which are, at irst glance, weightless, minor category. They are quite difficult to correctly determine, so these elements are presented in the categories of «note», a «framework text», «metatext expressions», «the author's speech,» etc. Verbal decoration refers to such speciic and multifaceted phenomena.